Erythrocyte Metabolic Reprogramming by Sphingosine 1-Phosphate in Chronic Kidney Disease and Therapies. Issue 3 (17th July 2020) - Xie, Tingting; Chen, Changhan; Peng, Zhangzhe; Brown, Benjamin C.; Reisz, Julie A.; Xu, Ping; Zhou, Zhen; Song, Anren; Zhang, Yujin; Bogdanov, Mikhail V.; Kellems, Rodney E.; D'Alessandro, Angelo; et al.
Abstract : Rationale: Hypoxia promotes renal damage and progression of chronic kidney disease (CKD). The erythrocyte is the only cell type for oxygen (O2 ) delivery. Sphingosine 1-phosphate (S1P)—a highly enriched biolipid in erythrocytes—is recently reported to be induced under high altitude in normal humans to enhance O2 delivery. However, nothing is known about erythrocyte S1P in CKD. Objective: To investigate the function and metabolic basis of erythrocyte S1P in CKD with a goal to explore potential therapeutics. Methods and Results: Using erythrocyte-specific SphK1 (sphingosine kinase 1; the only enzyme to produce S1P in erythrocytes) knockout mice ( eSphK1 −/− ) in an experimental model of hypertensive CKD with Ang II (angiotensin II) infusion, we found severe renal hypoxia, hypertension, proteinuria, and fibrosis in Ang II–infused eSphk1 −/− mice compared with controls. Untargeted metabolomics profiling and in vivo U- 13 C6 isotopically labeled glucose flux analysis revealed that SphK1 is required for channeling glucose metabolism toward glycolysis versus pentose phosphate pathway, resulting in enhanced erythroid-specific Rapoport-Luebering shunt in Ang II–infused mice. Mechanistically, increased erythrocyte S1P functioning intracellularly activates AMPK (AMP-activated protein kinase) 1α and BPGM (bisphosphoglycerate mutase) by reducing ceramide/S1P ratio and inhibiting PP2A (protein phosphatase 2A), leading to increased 2, 3-bisphosphoglycerate (an erythrocyte-specific metabolite negatively regulating Hb [hemoglobin]-O2 –binding affinity) production and thus more O2 delivery to counteract kidney hypoxia and progression to CKD. Preclinical studies revealed that an AMPK agonist or a PP2A inhibitor rescued the severe CKD phenotype in Ang II–infused eSphK1 −/− mice and prevented development of CKD in the control mice by inducing 2, 3-bisphosphoglycerate production and thus enhancing renal oxygenation. Translational research validated mouse findings in erythrocytes of hypertensive CKD patients and cultured human erythrocytes. Conclusions: Our study elucidates the beneficial role of eSphk1-S1P in hypertensive CKD by channeling glucose metabolism toward Rapoport-Luebering shunt and inducing 2, 3-bisphosphoglycerate production and O2 delivery via a PP2A-AMPK1α signaling pathway. These findings reveal the metabolic and molecular basis of erythrocyte S1P in CKD and new therapeutic avenues. Abstract : Supplemental Digital Content is available in the text.